Composer A. A. Egorov in the History of the Musical Culture of Chuvashia - Lyubov I. Bushueva (Publishing house "Sreda", 2022)
The article is devoted to the creative connections of the famous Soviet conductor and composer A.A. Egorov with the musical culture of Chuvashia in the 1930s. The purpose of the work is to recreate the historical picture of these connections, to determine his contribution to the Chuvash art and to identify the characteristic features of the interpretation of the national song folklore. The material of the study was musical texts of works by A.A. Egorov (first of all, the author's collection «Folk Songs Arranged for Mixed Choir by A. Egorov»), as well as his theoretical and methodological work in the field of choral arrangement of folklore primary sources. Using the analytical method, the author traces the history of the appearance of choral arrangements by A.A. Egorov on the themes of Chuvash folk songs, the musical and poetic text of the most popular work «Kolkhoz uy-khire» («Kukkuk») («Kolkhoz fields» («Kukushka», «Kukuk!")) is analyzed. It is concluded that the communication of A. A. Egorov with the head of the team the Chuvash composer V. P. Vorobyov inspired him to create ten miniatures for a cappella choir. Among the Chuvash adaptations, the most popular was «Kolkhoz uy-khire» («Kukkuk») - «Collective Farm Fields» («Kukushka»). Her undoubted success in the artistic culture of the 1930s let us explain not only the folklore theme successfully chosen by the composer, the organic interaction of the found methods of arranging the folklore source with the typical features of A. Egorov's creative style as a whole, but also the masterful use of all musical and expressive resources. Together with other works by A.A. Egorov's adaptation of «Kolkhoz uy-khire», included in the golden fund of Russian choral literature, can be called a classic of the musical art of Chuvashia.